The DESIGN FACTOR THE CAPABILITY LEVEL OF INFORMATION TECHNOLOGY GOVERNANCE AND RECOMMENDATIONS FOR IMPROVEMENT USING COBIT 2019: A CASE STUDY AT A PRIVATE UNIVERSITY IN PALEMBANG - Muhamad Yamin Achiruddin; Abdul Rahman (Information Technology and Science (ITScience), 2026)
Private university in Palembang that has utilized information technology to support its educational processes. This study demonstrates how COBIT 2019 design factors can be operationalized to identify strategically critical governance domains in higher education, shifting IT governance evaluation from generic domain assessment toward contextualized governance design, This study designs an information technology governance system based on COBIT 2019 and applies design factors to align governance objectives with university institutional context and strategic direction, thereby identifying priority domains and capability level targets that are most relevant to the university’s digital transformation. The application of these design factors highlights the EDM05 Ensure Stakeholder Engagement and BAI09 Manage Assets domains as the primary focus, as they are closely related to the need to enhance transparency in stakeholder involvement and to optimize IT asset management within the university environment. The study aims to assess the capability level of IT governance in the EDM05 and BAI09 domains, identify gaps between the current conditions and the targeted capability levels, and formulate improvement recommendations that are aligned with institutional needs and strategies. The research adopts a case study approach with a descriptive mixed method design, employing observation, interviews, and questionnaires, which are then analyzed using RACI Chart mapping, COBIT 2019 capability level measurement, and gap analysis to develop proposed process improvements. The findings indicate that the capability levels in both domains are still below the targeted levels, resulting in gaps related to stakeholder engagement, role and responsibility structures, IT performance reporting mechanisms, and IT asset lifecycle management. The implications of this research are the provision of a practical foundation for university in Palembang’s management to strengthen IT governance, as well as an academic contribution on the application of COBIT 2019 design factor–based governance in higher education institutions that can serve as a reference for other universities. Keywords : IT Governance, COBIT 2019, Capability, Recommendation